PELAYANAN KESEHATAN BAGI PASIEN BPJS (BADAN PENYELENGGARA JAMINAN SOSIAL) DI RUMAH SAKIT UMUM DAERAH KABUPATEN SIAK TAHUN 2016 - Novrialdi. J; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Patient satisfaction in health services is very important to note because it can describe the service in place of health services. Siak District General Hospital (RSUD) Siak is a C class state hospital located in Siak District. The hospital is able to provide limited specialist medical services. The decreasing and increasing number of patient visits BPJS every year, then the indication of a gap between services received with the expected BPJS patients at Siak Public Hospital (RSUD). He formulation of this research problem is: How the quality of health services for patients BPJS (Social Security Administering Body) at the Regional General Hospital of Siak Regency Year 2016? Data analysis method used in this research is descriptive qualitative analysis method that is trying to explain based on the phenomena that exist and trace all the facts related to the problems discussed based on the results of research that is Quality Health Services For Patients BPJS (Social Security Administering Body) At Home General Hospital of Siak Regency Year 2016. The result of the research stated that the health service for Patient BPJS (Social Security Administering Body) at Siak District General Hospital 2016, can be said is still low, that is on the punctuality of service, the process of health service use of computerized system is still low, Affairs will not be controlled properly, even lost so that can not be accounted for patients. On the ease of providing health services for Patients BPJS (Social Security Administering Body) at Siak District Public Hospital 2016, in terms of setting administrative requirements are still too rigid but in accordance with the rules set. On the accuracy of services still found the existence of discrimination in the provision of health services for Patients BPJS (Social Security Administering Body) at Siak District Public Hospital 2016. On the suitability of health services, BPJS Kab. Siak receive complaints and follow up until all the health services for the Patient BPJS (Social Security Administering Body) at Siak District Public Hospital 2016 has been completely finished.Keywords: Service, Health, BPJS, Kab. Siak.